High-strength non-polyolefin breathable film as well as preparation method and application thereof

By coating the polyamide cast film liquid on the non-polyolefin base film to form a porous film, the problem that the existing breathable film is difficult to take into account high strength, suitable breathability and microbial barrier properties, and a high-performance breathable film suitable for the medical packaging field is achieved.

CN119531144AActive Publication Date: 2025-02-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311091543.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-02-28
Estimated Expiration
2043-08-28

AI Technical Summary

Technical Problem

While the existing breathable membranes pursue high breathability and high strength, they are difficult to take into account the appropriate microbial barrier properties, resulting in limited application in the medical packaging field.

Method used

A non-polyolefin base film is used and a polyamide cast film liquid is coated on both sides of it, and a porous film is formed by phase separation in the solidification bath, thereby obtaining a breathable film with high strength, suitable breathability and good microbial barrier properties.

Benefits of technology

It has achieved a high-strength breathable film used in the medical packaging field, with suitable breathability, good microbial barrier properties and high strength, and broadened the application range of breathable film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004424071790000111
    Figure BDA0004424071790000111
  • Figure BDA0004424071790000131
    Figure BDA0004424071790000131
  • Figure BDA0004424071790000141
    Figure BDA0004424071790000141
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a high-strength non-polyolefin breathable film as well as a preparation method and application thereof. The non-polyolefin film comprises a base film and polyamide at least partially located on the two sides of the base film. Wherein the base film is made of non-polyolefin; the average pore size of the non-polyolefin film is between 0.5 [mu] m and 10 [mu] m. According to the method, non-polyolefin is used as a basement membrane, the two sides of the basement membrane are coated with a casting membrane solution of polyamide with specific appropriate concentration, then polyamide is coagulated on the basement membrane in a coagulating bath, and the membrane with appropriate air permeability, good microbial barrier property and good air permeability can be obtained according to the method. Meanwhile, the non-polyolefin film with high strength is suitable for the field of medical packaging, the source of the breathable film used in the field of medical packaging is greatly widened, and the non-polyolefin film has extremely high application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a high-strength non-polyolefin breathable film and a preparation method and application thereof. Background Art

[0002] Breathable film is a functional film material with a wide range of applications. It has important applications in the fields of medical packaging materials, medical protective clothing, building waterproofing and water treatment. In the field of medical packaging, in addition to ensuring the most basic microbial barrier properties, breathable films need to have both high air permeability and high strength. High air permeability is to better adapt to ethylene oxide sterilization methods, and high strength is to prevent packaging rupture and medical device failure during packaging, transportation and storage. However, usually, these two requirements are contradictory. In order to make the air permeability better, the film microstructure is usually looser, which easily reduces the strength and microbial barrier properties. Therefore, the breathable film should have appropriate air permeability to ensure good strength and microbial barrier properties. Under an average pressure difference of 1.23 kPa, the Gurley air permeability of the breathable film should be between 0.1 μm / (Pa·s) and 10 μm / (Pa·s). If the Gurley air permeability is greater than 10 μm / (Pa·s), it means that the air permeability is too good and the microbial barrier performance is too poor, and it cannot be used in the medical packaging field. If the Gurley air permeability is less than 0.1 μm / (Pa·s), it means that the air permeability is too poor and it cannot be applied to ethylene oxide sterilization, and it cannot be widely used in the medical packaging field.

[0003] The existing high-strength breathable membrane on the market is DuPont's Tyvek, which has air permeability that meets the requirements of ethylene oxide sterilization and has high strength. However, Tyvek is produced by polyethylene through flash spinning, which requires high temperature, high pressure and organic solvents in the production process. The production conditions are extremely harsh and it is only suitable for the production of polyolefin breathable membranes. Using non-polyolefin materials to prepare high-strength breathable membranes can broaden the application range of breathable membranes and realize their application in more fields. Summary of the invention

[0004] Based on this, the purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a high-strength non-polyolefin breathable film and its preparation method and application. Different from the flash spinning process to prepare polyolefin high-strength breathable film, the present invention constructs a breathable functional film on a non-polyolefin base film. Compared with the flash spinning process to prepare polyolefins, the non-polyolefin base film has smaller production conditions and is simpler. The preparation method of the present invention uses polyamide as the casting liquid, combined with the non-polyolefin base film, to obtain the high-strength non-polyolefin breathable film. The raw materials are easy to obtain and the method is simple. Not only that, the present invention overcomes the technical problem that conventional breathable films are not easy to coexist with suitable air permeability, high microbial barrier properties and high strength. The non-polyolefin breathable film of the present invention not only has suitable air permeability, but also has good microbial barrier properties, and at the same time has high strength, which is very suitable for the field of medical packaging and has extremely high promotion and application value.

[0005] The first aspect of the present invention is to provide a non-polyolefin film, which includes a base film and polyamide at least partially located on both sides of the base film; wherein the base film is made of non-polyolefin; and the average pore size of the non-polyolefin film is between 0.5μm and 10μm.

[0006] In a preferred embodiment of the present invention, the average pore size of the non-polyolefin film is 0.5 μm-5 μm, more preferably 0.5 μm-2 μm.

[0007] In a preferred embodiment of the present invention, at an average pressure difference of 1.23 kPa, the Gurley air permeability of the non-polyolefin film is not greater than 10 μm / (Pa·s) and not less than 0.1 μm / (Pa·s).

[0008] In a preferred embodiment of the present invention, the microbial barrier rating LRV of the non-polyolefin film is not less than 1.

[0009] In a preferred embodiment of the present invention, the thickness of the non-polyolefin film is not greater than 250 microns.

[0010] In a preferred embodiment of the present invention, the polyamide is at least one of nylon 6, nylon 612, nylon 66, and nylon 1212.

[0011] In a preferred embodiment of the present invention, the base membrane is a polymer membrane with strong polarity and high mechanical strength, including but not limited to a base membrane of at least one of PET non-woven fabric (PET is polyethylene terephthalate, also known as polyester resin), aramid paper, and nylon filter cloth.

[0012] As an example, when the substrate film is a PET non-woven fabric, the high-strength non-polyolefin breathable film provided by the present invention has a thickness of no more than 250 microns, a Gurley air permeability of no more than 10 μm / (Pa·s) and no less than 0.1 μm / (Pa·s) (average pressure difference is 1.23 kPa), a microbial barrier rating LRV of no less than 1, a tensile strength of no less than 20 MPa, a puncture strength of no less than 15 N, and a burst resistance of no less than 575 kPa. The high-strength non-polyolefin breathable film has a structural feature that the substrate is a high-strength and high-permeability PET non-woven fabric, and the surface of the substrate or the gaps between the fibers are filled with a porous film formed by polyamide.

[0013] The base film PET non-woven fabric has excellent air permeability, the Gurley air permeability is much greater than 10μm / (Pa·s) (cannot be detected by instruments), the tensile strength is not less than 20MPa, the puncture strength is not less than 15N, and the bursting resistance is not less than 575kPa. The filament PET non-woven fabric is preferably a fiber with an average diameter between 15μm and 25μm.

[0014] As an example, when the base membrane is aramid paper, the thickness of the high-strength non-polyolefin breathable film is not more than 180 microns, the Gurley air permeability is not more than 10 μm / (Pa·s) and not less than 0.1 μm / (Pa·s) (the average pressure difference is 1.23 kPa), the microbial barrier grade LRV is not less than 1, the tensile strength is not less than 25 MPa, the puncture strength is not less than 10 N, and the burst resistance is not less than 500 kPa.

[0015] The high-strength non-polyolefin breathable film has the structural feature that the substrate is a high-strength and high-permeability aramid paper, and the surface of the substrate or the gaps between fibers are filled with a porous film formed by polyamide.

[0016] The base film aramid paper has excellent air permeability, the Gurley air permeability is much greater than 10 μm / (Pa·s) (cannot be detected by instruments), the tensile strength is not less than 25 MPa, the puncture strength is not less than 10N, and the bursting resistance is not less than 500 kPa.

[0017] As an example, when the base film is a nylon filter cloth, the high-strength non-polyolefin breathable film provided by the present invention is characterized by a thickness of not more than 160 microns, a Gurley air permeability of not more than 10 μm / (Pa·s) and not less than 0.1 μm / (Pa·s) (average pressure difference is 1.23 kPa), a microbial barrier classification LRV of not less than 1, a tensile strength of not less than 30 MPa, a puncture strength of not less than 10 N, and a burst resistance of not less than 300 kPa. The nylon filter cloth is woven from nylon fibers, has excellent air permeability, and a Gurley air permeability far greater than 10 μm / (Pa·s) (cannot be detected by an instrument). The nylon filter cloth is preferably not less than 300 mesh, and more preferably not less than 400 mesh.

[0018] In a preferred embodiment of the present invention, the non-polyolefin film is obtained by the following preparation method: (1) firstly coating a first solution containing polyamide on one side of the substrate film, and then coagulating the polyamide on the substrate film in a coagulation bath;

[0019] (2) coating the other side of the film obtained in step (1) with a second solution containing polyamide, and then coagulating the polyamide on the film in a coagulation bath to obtain the non-polyolefin film;

[0020] Wherein, the mass concentration of polyamide in the first solution is 3%-10%; the mass concentration of polyamide in the second solution is 5%-30%.

[0021] The non-polyolefin film includes a base film and a polyamide at least partially located on both sides of the base film; wherein the porous film formed on the surface of the base or between the fiber gaps is a porous film formed by immersing the above-mentioned specific polyamide casting liquid in a polyamide poor solvent (also called a coagulation bath) to undergo phase separation, and the polyamide has good compatibility with the base film. Using the above-mentioned polyamide casting liquid in the specific concentration range can obtain a film with suitable air permeability, high microbial barrier properties and high strength.

[0022] The second aspect of the present invention is to provide a method for preparing the non-polyolefin film according to the first aspect, comprising the following steps:

[0023] (1) firstly coating a first solution containing polyamide on one side of the base film, and then coagulating the polyamide on the base film in a coagulation bath;

[0024] (2) coating the other side of the film obtained in step (1) with a second solution containing polyamide, and then coagulating the polyamide on the film in a coagulation bath to obtain the non-polyolefin film;

[0025] Wherein, the mass concentration of polyamide in the first solution is 3%-10%; the mass concentration of polyamide in the second solution is 5%-30%.

[0026] In a preferred embodiment of the present invention, the mass concentration of polyamide in the first solution is 5%-10%, preferably 5%-8%.

[0027] In a preferred embodiment of the present invention, the mass concentration of polyamide in the second solution is 10%-30%.

[0028] In a more preferred embodiment of the present invention, the mass concentration of polyamide in the first solution is 5%-10%, preferably 5%-8%, and the mass concentration of polyamide in the second solution is 10%-30%.

[0029] As mentioned above, preferably, the base film is at least one of PET non-woven fabric, aramid paper, and nylon filter cloth.

[0030] The concentration of the polyamide casting solution should be within a suitable range, so that the Gurley air permeability of the film is not greater than 10 μm / (Pa·s) and not less than 0.1 μm / (Pa·s) after being immersed in a coagulation bath and undergoing phase separation. In a preferred embodiment of the present invention, when the substrate film is a PET non-woven fabric, the mass concentration of the polyamide in the second solution is 10% to 30%, preferably 15% to 30%, more preferably 20% to 30%; and / or, the mass concentration of the polyamide in the first solution is 5%-10%, preferably 5%-8%.

[0031] When the substrate film is aramid paper, the mass concentration of polyamide in the second solution is 10% to 20%, preferably 15% to 20%, and / or the mass concentration of polyamide in the first solution is 5%-10%, preferably 5%-8%.

[0032] When the substrate membrane is nylon filter cloth, the mass concentration of polyamide in the second solution is 10%-20%, preferably 15%-20%, and / or the mass concentration of polyamide in the first solution is 5%-10%, preferably 5%-8%.

[0033] The porous membrane formed after the phase separation has an average pore size between 0.5 μm and 10 μm, more preferably between 0.5 μm and 5 μm, and more preferably between 0.5 μm and 2 μm.

[0034] In a preferred embodiment of the present invention, the coagulation baths in step (1) and step (2) are the same or different, and each is at least one of water, ethanol, methanol, and acetone.

[0035] In a preferred embodiment of the present invention, the first solution and the second solution are respectively solutions formed by dissolving polyamide in formic acid, methanol / CaCl2, and ethanol / CaCl2.

[0036] The polyamide casting liquid is a solution of polyamide in its good solvent. The polyamide good solvent is preferably formic acid, methanol / CaCl2 or ethanol / CaCl2 in a mass ratio of 4:1. The coagulation bath is a solvent that cannot dissolve polyamide alone and is miscible with the good solvent mentioned above. The polyamide coagulation bath is preferably water, a mixed solvent of water / ethanol, water / methanol, and water / acetone in any proportion.

[0037] When the base membrane is a nylon filter cloth, not all polyamide solutions can be used as casting solutions to obtain non-polyolefin films with excellent performance. For example, when the casting solution is a solution formed by polyamide dissolved in formic acid, coating it on the surface of the nylon filter cloth will cause part of the nylon filter cloth to dissolve or be etched, resulting in higher air permeability and lower microbial barrier rating. After research, the inventors of the present invention found that in a preferred embodiment of the present invention, when the base membrane is a nylon filter cloth, the first solution and the second solution are each a solution formed by polyamide dissolved in methanol / CaCl2 or ethanol / CaCl2.

[0038] In a preferred embodiment of the present invention, the coating method is scraping. Preferably, the distance between the lower edge of the scraping device and the base film does not exceed 50 μm, more preferably does not exceed 40 μm, and more preferably does not exceed 30 μm.

[0039] In a preferred embodiment of the present invention, the steps (1) and (2) further include the step of drying the obtained film after the polyamide is coagulated on the film in a coagulation bath.

[0040] As an example, in a more preferred embodiment of the present invention, the preparation method of the above-mentioned high-strength non-polyolefin breathable film is described in detail as follows:

[0041] Step 1: uniformly coating a polyamide casting solution (ie, the first solution) having good compatibility with the PET substrate film on one side of the PET substrate film having high strength and high air permeability.

[0042] The high-strength and high-permeability PET base film has excellent air permeability, the Gurley air permeability is much greater than 10μm / (Pa·s) (cannot be detected by instruments), the tensile strength is not less than 20MPa, the puncture strength is not less than 15N, and the burst resistance is not less than 575kPa. The filament PET non-woven fabric is preferably a fiber with an average fiber diameter between 15μm and 25μm.

[0043] The polyamide casting solution is a solution in which polyamide is dissolved in its good solvent, and the polyamide is at least one of nylon 6, nylon 612, nylon 66, and nylon 1212. The polyamide good solvent is preferably formic acid, methanol / CaCl2 or ethanol / CaCl2 with a mass ratio of 4:1. The concentration of the casting solution should be in a suitable range, so that the Gurley air permeability of the film is not more than 30μm / (Pa·s) and not less than 10μm / (Pa·s) after being immersed in a coagulation bath for phase separation. For the PET substrate film, the mass concentration of the polyamide in the first solution is preferably 3% to 10%, more preferably 5% to 10%, and more preferably 5% to 8%.

[0044] The coating process is preferably carried out by scraping, and the distance between the film applicator or scraper and the substrate is preferably not more than 40 μm, more preferably not more than 30 μm.

[0045] Step 2: Immerse the coated basement membrane in a coagulation bath. After a period of time, take out the basement membrane, wash and dry it.

[0046] The coagulation bath is a poor solvent for polyamide and is miscible with a good solvent for polyamide. The coagulation bath is preferably water, a mixed solvent of water / ethanol, water / methanol, or water / acetone in any proportion.

[0047] The time for which the coated substrate film is immersed in the coagulation bath is not strictly limited, but is preferably not more than 10 minutes, more preferably not more than 5 minutes.

[0048] Step 3: The uncoated side of the dried membrane is then evenly coated with a polyamide casting solution (ie, the second solution) having good compatibility with the membrane.

[0049] The polyamide casting solution is the same as that in step 2, and the concentration of the casting solution should be within a suitable range, so that the Gurley air permeability of the final film is not greater than 10 μm / (Pa·s) and not less than 0.1 μm / (Pa·s) after being immersed in a coagulation bath and undergoing phase separation. For a PET substrate film, the mass concentration of the polyamide in the second solution is preferably 10% to 30%, more preferably 10% to 20%, and more preferably 15% to 20%.

[0050] Step 4: Immerse the membrane in the coagulation bath again. After a period of time, take out the membrane, wash and dry it.

[0051] The third aspect of the present invention is to provide an application of the non-polyolefin film described in the first aspect or the non-polyolefin film obtained by the preparation method described in the second aspect in the field of medical materials.

[0052] The non-polyolefin breathable film of the present invention not only has suitable air permeability, but also has good microbial barrier properties and high strength, and is very suitable for the field of medical packaging, and has extremely high promotion and application value.

[0053] As mentioned above, general non-polyolefins are used as base films, such as non-polyolefin PET non-woven fabrics, aramid paper, nylon filter cloth, etc., because their air permeability is much greater than 10μm / (Pa·s), and they have high air permeability, but poor microbial barrier properties or no microbial barrier properties at all. In the prior art, it is difficult to prepare such materials into films with suitable air permeability and high microbial barrier properties. Even if the air permeability of such films is reduced by coating other polymers, direct coating of polymers can easily cause the film to lose its air permeability. Therefore, it is very difficult to use such non-polyolefins as base films to obtain films with suitable air permeability, high microbial barrier properties and high strength.

[0054] The inventors of the present invention unexpectedly discovered through research that by using the above-mentioned non-polyolefin as a base film, coating both sides of the base film with a specific suitable concentration of polyamide casting liquid, and then solidifying the polyamide on the base film in a coagulation bath, a non-polyolefin film with suitable air permeability, good microbial barrier properties, and high strength can be obtained according to this method. The film is suitable for the field of medical packaging, greatly broadens the source of breathable films used in the field of medical packaging, and has extremely high application value. DETAILED DESCRIPTION

[0055] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0056] The present invention is further described below in conjunction with the embodiments. The scope of the present invention is not limited by these embodiments, but is set forth in the appended claims.

[0057] The Gurley air permeability is determined in accordance with the provisions of GB / T 458-2008, the microbial barrier grading test is tested in accordance with the provisions of YY / T0681.10-2011, the tensile strength is determined in accordance with the provisions of GB / T 1040.3-2006, the puncture strength is determined in accordance with the provisions of GB / T10004-2008, and the burst resistance is determined in accordance with the provisions of GB / T 454-2020.

[0058] Test method for average pore size: The average pore size is tested by the bubble point method. The instrument used for the test is the PSDA-30 pore size analyzer of Nanjing Gaoqian Functional Materials Technology Co., Ltd. The test method refers to GB / T32361-2015.

[0059] PET filament spunbond nonwoven fabric was purchased from Shanghai Tianlue Textile New Materials Co., Ltd. with a thickness of 190 μm.

[0060] Example 1A

[0061] A commercially available PET filament spunbond nonwoven fabric was coated with a nylon 6 formic acid solution at a concentration of 5wt% on one side, then immersed in water for coagulation, taken out and naturally dried, and a nylon 6 formic acid solution at a concentration of 10wt% was coated on the other side of the obtained film, immersed in water again for coagulation, taken out and naturally dried. The above coating methods were all blade coating, and the distance between the film applicator and the substrate was 30μm.

[0062] The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested. The results are shown in Table 1.

[0063] After testing, the average pore size of the high-strength non-polyolefin breathable film is 8.5 μm and the thickness is 200 μm.

[0064] In the present invention, in the following examples and comparative examples, all coating methods are scraping, and the distance between the film applicator and the substrate is 30 μm.

[0065] Example 2A

[0066] A commercially available PET filament spunbond nonwoven fabric was coated with a nylon 6 formic acid solution at a concentration of 5wt% on one side, then immersed in water for coagulation, taken out and naturally dried. A nylon 6 formic acid solution at a concentration of 15wt% was coated on the other side of the obtained film, and then immersed in water for coagulation again, taken out and naturally dried.

[0067] The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested. The results are shown in Table 1.

[0068] Example 3A

[0069] A commercially available PET filament spunbond nonwoven fabric was coated with a nylon 6 formic acid solution at a concentration of 5wt% on one side, then immersed in water for coagulation, taken out and naturally dried, and a nylon 6 formic acid solution at a concentration of 20wt% was coated on the other side of the obtained film, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 1.

[0070] Example 4A

[0071] A commercially available PET filament spunbond nonwoven fabric was coated with a nylon 6 formic acid solution at a concentration of 5wt% on one side, then immersed in water for coagulation, taken out and naturally dried, and a nylon 6 formic acid solution at a concentration of 30wt% was coated on the other side of the obtained film, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 1.

[0072] Example 5A

[0073] A commercially available PET filament spunbond nonwoven fabric was coated with a nylon 612 formic acid solution at a concentration of 5wt% on one side, then immersed in water for coagulation, taken out and naturally dried, and a nylon 612 formic acid solution at a concentration of 15wt% was coated on the other side of the obtained film, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 1.

[0074] Example 6A

[0075] A commercially available PET filament spunbond nonwoven fabric was coated on both sides with a nylon 66 formic acid solution at a concentration of 5wt%, then immersed in water for coagulation, taken out and naturally dried, and the other side of the obtained film was coated with a nylon 66 formic acid solution at a concentration of 15wt%, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 1.

[0076] Example 7A

[0077] A commercially available PET filament spunbond nonwoven fabric was coated on both sides with a 5wt% formic acid solution of nylon 1212, then immersed in water for coagulation, taken out and naturally dried, and the other side of the obtained film was coated with a 15wt% formic acid solution of nylon 1212, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 1.

[0078] Comparative Example 1A

[0079] The commercially available PET filament spunbond nonwoven fabric was not treated in any way and its average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested. The results are shown in Table 1.

[0080] Comparative Example 2A

[0081] A commercially available PET filament spunbond nonwoven fabric was coated with a nylon 6 formic acid solution at a concentration of 10 wt % on one side, then immersed in water for coagulation, taken out and naturally dried, and the average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested. The results are shown in Table 1.

[0082] Comparative Example 3A

[0083] A commercially available PET filament spunbond nonwoven fabric was coated with a nylon 6 formic acid solution at a concentration of 25 wt % on one side, then immersed in water for coagulation, taken out and naturally dried, and the average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested. The results are shown in Table 1.

[0084] Comparative Example 4A

[0085] A commercially available PET filament spunbond nonwoven fabric was coated with a 15wt% nylon 6 formic acid solution on one side, then immersed in water for coagulation, taken out and naturally dried. A 15wt% nylon 6 formic acid solution was coated on the other side of the obtained film, then immersed in water for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested. The results are shown in Table 1.

[0086] Table 1

[0087]

[0088] The technical effect of the present invention is described below using aramid paper as the base film.

[0089] Aramid paper was purchased from Yantai Minshida Special Paper Co., Ltd. with a thickness of 130 μm.

[0090] Example 1B

[0091] A commercially available aramid paper is coated with a 3wt% nylon 6 formic acid solution on one side, then immersed in water for coagulation, taken out and naturally dried. A 10wt% nylon 6 formic acid solution is coated on the other side of the obtained film, then immersed in water for coagulation again, taken out and naturally dried.

[0092] The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested. The results are shown in Table 2.

[0093] Example 2B

[0094] A commercially available aramid paper was coated with a nylon 6 formic acid solution at a concentration of 5wt% on one side, then immersed in water for coagulation, taken out and naturally dried, and a nylon 6 formic acid solution at a concentration of 10wt% was coated on the other side of the obtained film, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 2.

[0095] Example 3B

[0096] A commercially available aramid paper was coated with a 10 wt% formic acid solution of nylon 6 on one side, then immersed in water for coagulation, taken out and naturally dried, and a 10 wt% formic acid solution of nylon 6 was coated on the other side of the obtained film, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 2.

[0097] Example 4B

[0098] A commercially available aramid paper was coated with a nylon 6 formic acid solution at a concentration of 5wt% on one side, then immersed in water for coagulation, taken out and naturally dried, and a nylon 6 formic acid solution at a concentration of 15wt% was coated on the other side of the obtained film, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 2.

[0099] Example 5B

[0100] A commercially available aramid paper was coated with a nylon 6 formic acid solution at a concentration of 5wt% on one side, then immersed in water for coagulation, taken out and naturally dried, and a nylon 6 formic acid solution at a concentration of 20wt% was coated on the other side of the obtained film, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 2.

[0101] Comparative Example 1B

[0102] The commercially available aramid paper was not treated in any way and its average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested. The results are shown in Table 2.

[0103] Comparative Example 2B

[0104] A commercially available aramid paper was coated with a nylon 6 formic acid solution at a concentration of 2wt% on one side, then immersed in water for coagulation, taken out and naturally dried, and a nylon 6 formic acid solution at a concentration of 10wt% was coated on the other side of the obtained film, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 2.

[0105] Comparative Example 3B

[0106] A commercially available aramid paper was coated with a nylon 6 formic acid solution at a concentration of 15 wt %, then immersed in water for coagulation, taken out and naturally dried, and the other side of the obtained film was coated with a nylon 6 formic acid solution at a concentration of 10 wt %, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 2.

[0107] Table 2

[0108]

[0109]

[0110] The technical effect of the present invention is described below using nylon filter cloth as the base membrane.

[0111] Example 1C

[0112] A commercially available 300-mesh nylon filter cloth was coated on one side with a methanol / CaCl2 solution of nylon 6 (methanol to CaCl2 mass ratio of 4:1) with a nylon 6 concentration of 3wt%, then immersed in water for coagulation, taken out and naturally dried; the other side of the obtained film was coated with a methanol / CaCl2 solution of nylon 6 (methanol to CaCl2 mass ratio of 4:1) with a nylon 6 concentration of 10wt%, then immersed in water for coagulation again, taken out and naturally dried.

[0113] The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested. The results are shown in Table 3.

[0114] Example 2C

[0115] A commercially available 300-mesh nylon filter cloth was coated with a methanol / CaCl2 solution of nylon 6 (methanol to CaCl2 mass ratio of 4:1) on one side, with a nylon 6 concentration of 5wt%, then immersed in water for coagulation, taken out and naturally dried, and the other side of the obtained film was coated with a methanol / CaCl2 solution of nylon 6 (methanol to CaCl2 mass ratio of 4:1) with a nylon 6 concentration of 10wt%, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 3.

[0116] Example 3C

[0117] A commercially available 300-mesh nylon filter cloth was coated with a methanol / CaCl2 solution of nylon 6 (methanol to CaCl2 mass ratio of 4:1) on one side, with a nylon 6 concentration of 10wt%, then immersed in water for coagulation, taken out and naturally dried, and the other side of the obtained film was coated with a methanol / CaCl2 solution of nylon 6 (methanol to CaCl2 mass ratio of 4:1) with a nylon 6 concentration of 10wt%, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 3.

[0118] Example 4C

[0119] A commercially available 300-mesh nylon filter cloth was coated with a methanol / CaCl2 solution of nylon 6 (methanol to CaCl2 mass ratio of 4:1) on one side, with a nylon 6 concentration of 5wt%, then immersed in water for coagulation, taken out and naturally dried, and the other side of the obtained film was coated with a methanol / CaCl2 solution of nylon 6 (methanol to CaCl2 mass ratio of 4:1) with a nylon 6 concentration of 15wt%, immersed in water again for coagulation, taken out and naturally dried. The average pore size, Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 3.

[0120] Example 5C

[0121] A commercially available 300-mesh nylon filter cloth was coated with a methanol / CaCl2 solution of nylon 6 (methanol to CaCl2 mass ratio of 4:1) on one side, with a nylon 6 concentration of 5wt%, then immersed in water for coagulation, taken out and naturally dried, and the other side of the obtained film was coated with a methanol / CaCl2 solution of nylon 6 (methanol to CaCl2 mass ratio of 4:1) with a nylon 6 concentration of 20wt%, immersed in water again for coagulation, taken out and naturally dried. Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 3.

[0122] Comparative Example 1C

[0123] The commercially available 300-mesh nylon filter cloth was tested for Gurley air permeability, microbial barrier grade and mechanical properties without any treatment. The results are shown in Table 3.

[0124] Comparative Example 2C

[0125] A commercially available 300-mesh nylon filter cloth was coated with a methanol / CaCl2 solution of nylon 6 (methanol to CaCl2 mass ratio of 4:1) on one side, with a nylon 6 concentration of 2wt%, then immersed in water for coagulation, taken out and naturally dried, and the other side of the obtained film was coated with a methanol / CaCl2 solution of nylon 6 (methanol to CaCl2 mass ratio of 4:1) with a nylon 6 concentration of 10wt%, immersed in water again for coagulation, taken out and naturally dried. Gurley air permeability, microbial barrier grade and mechanical properties were tested, and the results are shown in Table 3.

[0126] Table 3

[0127]

[0128]

[0129] From Comparative Example 1 (including A, B, and C), it can be seen that the air permeability of conventional PET nonwoven fabrics, aramid paper, and nylon filter cloth is too high, and the microbial barrier property is poor or completely absent. From the remaining comparative examples, it can be seen that when the polymer is coated on the base film, if the concentration is not selected properly, the air permeability of the film cannot reach an appropriate level, making it impossible to have good air permeability and microbial barrier properties at the same time.

[0130] It can be seen from the above embodiments of the present invention that a polyamide casting liquid with a specific suitable concentration is coated on both sides of the base membrane, and then the polyamide is coagulated on the base membrane in a coagulation bath. According to this method, a non-polyolefin film with suitable air permeability, good microbial barrier properties and high strength can be obtained, achieving unexpected technical effects.

[0131] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

[0132] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0133] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0134] The endpoints and any values ​​of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, between the endpoint values ​​of each scope, between the endpoint values ​​of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.

[0135] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

[0136] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.

Claims

1. A non-polyolefin film, comprising a substrate film and a polyamide at least partially located on both sides of the substrate film; in, The material of the base film is non-polyolefin; The average pore size of the non-polyolefin membrane is between 0.5 μm and 10 μm.

2. The non-polyolefin film according to claim 1, characterized in that: The average pore size of the non-polyolefin membrane is 0.5 μm-5 μm, preferably 0.5 μm-2 μm; and / or, At an average pressure difference of 1.23 kPa, the Gurley air permeability of the non-polyolefin membrane is not greater than 10 μm / (Pa·s) and not less than 0.1 μm / (Pa·s); and / or, The microbial barrier rating LRV of the non-polyolefin membrane is not less than 1; and / or, The thickness of the non-polyolefin film is no greater than 250 microns.

3. The non-polyolefin film according to claim 1, characterized in that: The polyamide is at least one of nylon 6, nylon 612, nylon 66, and nylon 1212; and / or The base film is at least one of PET non-woven fabric, aramid paper and nylon filter cloth.

4. A non-polyolefin film according to any one of claims 1 to 3, characterized in that: The non-polyolefin film is obtained by the following preparation method: (1) firstly coating a first solution containing polyamide on one side of the base film, and then coagulating the polyamide on the base film in a coagulation bath; (2) coating the other side of the film obtained in step (1) with a second solution containing polyamide, and then coagulating the polyamide on the film in a coagulation bath to obtain the non-polyolefin film; Wherein, the mass concentration of polyamide in the first solution is 3%-10%; The mass concentration of polyamide in the second solution is 5%-30%.

5. A method for preparing a non-polyolefin film according to any one of claims 1 to 4, comprising the following steps: (1) firstly coating a first solution containing polyamide on one side of the base film, and then coagulating the polyamide on the base film in a coagulation bath; (2) coating the other side of the film obtained in step (1) with a second solution containing polyamide, and then coagulating the polyamide on the film in a coagulation bath to obtain the non-polyolefin film; Wherein, the mass concentration of polyamide in the first solution is 3%-10%; The mass concentration of polyamide in the second solution is 5%-30%.

6. The preparation method according to claim 5, characterized in that: The mass concentration of polyamide in the first solution is 5%-10%, preferably 5%-8%; and / or, The mass concentration of polyamide in the second solution is 10%-30%.

7. The preparation method according to claim 5, characterized in that: The base film is at least one of PET non-woven fabric, aramid paper, and nylon filter cloth; and / or, The coagulation baths in step (1) and step (2) are the same or different, and each is at least one of water, ethanol, methanol, and acetone.

8. The preparation method according to claim 5, characterized in that: The first solution and the second solution are each a solution of polyamide dissolved in formic acid, methanol / CaCl2, or ethanol / CaCl2; preferably, When the base membrane is a nylon filter cloth, the first solution and the second solution are respectively solutions formed by dissolving polyamide in one of methanol / CaCl 2 and ethanol / CaCl 2 .

9. The preparation method according to any one of claims 5 to 8, characterized in that: The coating method is scraping, preferably, the distance between the lower edge of the scraping device and the base film does not exceed 50 μm, more preferably does not exceed 40 μm, and most preferably does not exceed 30 μm; and / or, The method further comprises steps (1) and (2) of coagulating the polyamide on the film in a coagulation bath, and then drying the obtained film.

10. Use of the non-polyolefin film according to any one of claims 1 to 4 or the non-polyolefin film obtained by the preparation method according to any one of claims 5 to 9 in the field of medical materials.

Citation Information

Patent Citations

  • Preparation method of nanofiltration membrane for dye concentration and desalination

    CN102451622A

  • Production method of cloth with microporous film coating

    CN1059002A

  • Halogen-free or low-halogen polyamide coated fabric and preparation method thereof

    CN114075792A

  • Microporous barrier and preparing method thereof

    CN1552508A

  • Menufacturing method of meta-aramid based porous membrane for secondary battery and porous membrane thereby

    KR1020130073194A